NEURONAL SIGNALING - Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2015)
Intracellular processes in neurons begins when the extracellular chemical signals such as neurotransmitters, attached at specific receptors which then activates a cascade of intracellular reactions included herein are proteins GTP, second messengers, protein kinases, ion channels, and other effector proteins that will change the instantaneous state of the physiology of the cell the target. The intracellular signal will also change the long-term performance by interfering with the transcription of genes that will change the protein composition of the target cell. Many components are involved in intracellular signal that will control the neurons, so that the necessary coordination of electrical and chemical signals in the nervous system. Also discussed here regarding the conducting various signals in neurons, including signaling pathways, type receptors, G proteins and molecular targets, second messengers, the target of second messengers, NGF/TrkA, long-term depression (LTD), and tyrosine phosphorylation hidrosilase.Â